ANALISIS SEMIOTIKA PESAN DAKWAH DALAM WEB SERIES USTADZ MILLENIAL - Fitri Meliya Sari (Universitas Teuku Umar, 2022)
The Web Series “Ustadz Millenial” tells the story of a life that tells the story of the life of a young man who aspires to become a young ustadz. However, his family's troubles and death are his dreams. But he still tries to realize his ideals by preaching through social media. Based on the background above, the purpose of this study is to answer how the signified and the signifier as well as the object (referent) are displayed in the series